How Gender Conscious Pedagogy in Higher Education Can Stimulate Actions of Social Justice in Society - Witt, Ann-Katrin (2014)
In order to reflect about methods that can generate social justice and democratization, this article emphasises on practical implementations, connected to gender conscious pedagogy. Gender conscious pedagogy aims at overcoming the myth of objectivity, and by questioning through teaching what is considered as common sense and ‘normal’. This entails acting and reflecting on breakthroughs, for example about an understanding of how gender codes influence everyday instances as well as working life. The collected data is based on narratives from alumni students who were asked to memorise and reflect on their gender studies and particularly about how useful this type of knowledge is in connection with everyday and working life - as politician, lecturer, IT-manager, doctoral student etc. The aim of this article is to focus on how teachers support students to be gender confident and as a consequence of that, becoming gender actors outside the university, in working life. Some central questions are: how are gender issues represented and integrated in the different areas of studies; what can teachers do in order to generate equality in the classroom; in what way and how are students given possibilities of understanding, internalizing and discussing gender issues.